Fabrication of Fe3O4/SiO2 core/shell nanoparticles attached to graphene oxide and its use as an adsorbent - Yao, Yunjin.; Miao, S.; Yu, S.; Li, Ping; Sun, Hongqi; Wang, Shaobin (Academic Press, 2012)
Amino-functionalized Fe3O4/SiO2 core/shell nanoparticles were synthesized by reacting Fe3O4 nanoparticles with tetraethyl orthosilicate and (3-aminopropyl) triethoxysilane to introduce amino groups on the surface. The amino groups on the Fe3O4/SiO2 were reacted with the carboxylic groups of graphene oxide (GO) with the aid of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinnimide to form Fe3O4/SiO2––GO nanoparticles. The structural, surface, and magnetic characteristics of the material were investigated by scanning and transmission electron microscopy, energy-dispersive X-ray spectrometry, powder X-ray diffraction, Fourier transform infrared spectroscopy, and thermogravimetric analysis. Adsorption equilibrium and kinetics of methylene blue on the Fe3O4/SiO2––GO were studied in a batch system. The maximum adsorption capacities were found to be 97.0, 102.6, and 111.1 mg g−1 at 25, 45, and 60 °C, respectively. A second-order kinetic equation could best describe the sorption kinetics. Thermodynamic parameters indicated that the adsorption of methylene blue onto the material was thermodynamically feasible and could occur spontaneously.